Acute Chest Syndrome Progressing to ARDS in a Patient of 25-Week Gestation - Jefferson Chambers; Nichole Smith; Matthew Sehring; Subramanyam Chittivelu (Case Reports in Critical Care)
Acute chest syndrome is a complication of sickle cell disease and represents the highest cause of mortality in those afflicted with the disorder. Pregnancy represents an increased risk for complications of sickle cell disease in both the mother and fetus. We present a case of a 20-year-old patient with known sickle cell disease who was at 25-week gestation and developed acute chest syndrome refractory to conventional therapies and requiring emergency cesarean section. Following delivery, the patient developed acute respiratory distress syndrome (ARDS) requiring extracorporeal membrane oxygenation (ECMO). The patient and infant eventually made full recoveries. This case highlights the importance of aggressive management of ACS and careful monitoring in a pregnant patient.